D-mannose suppresses macrophage IL-1β production - Simone Torretta (Nature Portfolio, 2020)
Mannose is present at trace levels in blood and regulates cancer growth. Here the authors show that supraphysiological levels of mannose can also regulate macrophages, limiting their production of IL-1β and increasing resistance of mice to LPS-induced endotoxemia and DSS-induced colitis.